Does life have meaning, or is it self‐deception at best and terrifyingly absurd at worst?. Issue 1 (6th June 2018) - Ruse, Michael
Abstract: A discussion of the meaning of life takes many twists and turns in an exploration of what great minds from several centuries have had to say regarding this question.